High power led thermal dissipation analysis via slug and heat sink - Rajendran, Vairavan
High power light emitting diode (LED), are captivating attention in recent times due to its cogent impacts on lighting industry in terms of efficacy, low power consumption, long lifetime and miniature physical size. However, the high junction temperature of the high power light emitting diodes continues to be a key issue in the LED industry as it significantly influences the reliability and efficiency of the LED. In this research, the thermal dissipation of a single chip high power light emitting diode package were evaluated and analyzed through simulation. The prime focus of this research is placed on the heat slug of the LED package and its effect on the LED chip in terms of junction temperature, Von Mises stress and thermal resistances. The variation of the heat slug was done in terms of size, slug material and shape. In addition, the effect of heat sink design in terms of fin numbers and its influence on the junction temperature of the LED was also investigated. The research was carried out using Ansys version 11. For the first part of the research, the heat slug variation analysis was done. The single chip LED package was powered with input power ranging from 0.1 W to 1 W. Two types of heat slug shape; rectangular and cylindrical with varied dimension were used . Three types of heat slug material, aluminum, copper and copper diamond was used and the heat dissipation was compared. The simulation was carried out under four types of conduction condition; natural convection condition, h = 5 W /m2C and three forced convection condition,h = 10 W/m2C, 15 W/m2C and 20 W/m2C respectively. In the second part of this research, heat sink fin number variation analysis was done. The single chip LED package was varied by different heat sink design in terms of fin numbers ranging from four fins to 20 fins. The key findings of heat slug variation analysis in terms of heat slug shape, size and material at input power of 1 W showed that the LED package with 1 = 5 rnm, w = 5 nun, h = 1 mm rectangular copper diamond composite heat slug, under forced convection condition of h = 20 W/m2C exhibited the best thermal performance with junction temperature of 56.01 °C with significant reduction of 53.10 % in terms of junction temperature. In addition, the heat sink fin number analysis showed that the LED package with 1 = 5 mm, w = 5 mm, h = 1 mm rectangular copper diamond composite heat slug, under forced convection condition, h = 20 W/m2C with 20 fm heat sink exhibited the best thermal performance with junction temperature of 44.84 °C with significant reduction of 19.94 % in terms of junction temperature.